Tax-price elasticity of charitable donations – evidence from the German taxpayer panel - Maja Adena (The Routledge Handbook of Taxation and Philanthropy, 2021)
I estimate permanent and transitory tax-price and income elasticity of charitable giving in Germany using a rich panel data of tax return for the years 2001–2006. Income tax reforms were implemented in 2004 and 2005. The results suggest that the permanent tax-price elasticity varies significantly by income class, ranging from –0.2 for low incomes to –1.6 for higher incomes. Permanent income elasticity does not vary much among income classes, is rather low, and ranges between 0.2 and 0.3. The donors adjust their donations gradually after changes in the tax schedule and respond to future predictable changes in price. They respond to changes in current and, to a smaller extent, future income.
Keywords: 330